Transcriptome landscape of the adrenal gland and superior cervical ganglion from hypertension-induced left ventricular hypertrophy rat model - Chaohong Li; Fengting Liu; Xingyu Li; Xiaohua Yang; Qiaoqiao Li; Jing Huang (BMC Genomics)
Abstract Background Hypertension-induced left ventricular hypertrophy (LVH) is a cardiac structural remodeling and dysfunction resulting from chronic hypertension and is an independent risk factor for cardiovascular morbidity and mortality. Studies have implicated the involvement of the adrenal gland (AG) and superior cervical ganglion (SCG) in hypertension regulation. However, the molecular mechanisms of AG and SCG during hypertension-induced LVH remain unclear. In this study, we investigated the transcriptome characteristics of the left ventricle, AG, and SCG in 24-week-old spontaneously hypertensive rats (SHR) and Wistar-Kyoto (WKY) rats using transcriptome sequencing (RNA-seq) technology. Results We identified 671 differentially expressed genes (DEGs) in the left ventricle, 1596 DEGs in the AG, and 343 DEGs in the SCG between SHR and WKY rats. Functional analysis revealed that these DEGs were involved in pathways related to immune inflammation, cellular senescence, metabolic responses, and synaptic transmission. We also identified the top 20 hub genes specific to each of the three organs. PPI network analysis showed that these hub genes were highly interconnected and clustered into three functional modules. KEGG pathway analysis revealed that the hub genes in the left ventricle and AG were mainly enriched in inflammation-related pathways, while the hub genes in the SCG were primarily enriched in synapse-related pathways. Venn diagram analysis identified 63 overlapping DEGs across the three organs, with 59 DEGs exhibiting consistent expression changes. Conclusions In summary, our study elucidates the transcriptome features of AG and SCG during hypertension-induced LVH in SHR.